NMR Solution Structure of the Protein PsbQ from Photosystem II. - Rathner, Petr (Jihočeská univerzita, 2013)
The PsbQ protein (16.5 kDa) is an extrinsic protein found in the thylakoid membrane of higher plants and green algae. As a member of the Psb protein family, it is situated in the oxygen evolving center and takes part in the water splitting reaction. The stable oxygen production in photosystem II depends on the cooperation of PsbQ with other photosynthetic proteins, mainly PsbP. In order to identify the possible interaction sites, the tertiary structure in solution has to be determined. Although the X-ray crystallographic structure of PsbQ was determined previously, the conformation of residues 14-33 (so-called "missing link") was still unknown at the onset of this work. The initial backbone assignment as well as a secondary structure estimation were achieved recently. In this thesis the resonance assignment was extended and 15N as well as 13C NOESY-HSQC spectra were recorded to obtain structural constraints. The solution structure was determined using the program CYANA. The results obtained show that, while the four helix bundle domain is nearly identical compared to the available X-Ray crystallographic structure significant deviations occur in the N-terminal region. In particular, the residues 37-41, where a short ?-strand had been proposed in the crystal structure, exhibit high ?-helical propensity.
NMR Solution Structure of the Protein PsbQ from Photosystem II.
Keywords: PsbQ; Photosystem II; NMR; solution structure; PsbQ; Photosystem II; NMR; solution structure